Oral Mucosa in Health and Disease A Concise Handbook (Springer International Publishing, 2018)
This book is designed to re-establish the position of the oral cavity and its mucosa at the forefront of defence and maintenance of homeostatic mechanisms that protect against disease not just locally but also systemically. The oral mucosa is a unique collection of tissues that constitutes a highly active environment with its own unique microflora and homeostatic interaction with the innate and adaptive immune responses. As an immune tissue the oral mucosa was somewhat neglected in the past owing to the tendency to assume similarity to the gut mucosa. More recently it has become apparent that the oral mucosa is a complex environment and, like the esophageal mucosa, has more in common with vaginal tissue than with the gut. Furthermore, the ability of the oral mucosa to act as an immune inductive site has made it an attractive area of research in terms of desensitization for allergic reactions and possibly autoimmune responses. In this book, recognized experts in the field provide up-to-date coverage of all aspects of the structure and function of the oral mucosa, reflecting important recent advances in knowledge, including at the molecular level.